2020
DOI: 10.1186/s12859-020-03706-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive host-pathogen protein-protein interaction network analysis

Abstract: Background Infectious diseases are a cruel assassin with millions of victims around the world each year. Understanding infectious mechanism of viruses is indispensable for their inhibition. One of the best ways of unveiling this mechanism is to investigate the host-pathogen protein-protein interaction network. In this paper we try to disclose many properties of this network. We focus on human as host and integrate experimentally 32,859 interaction between human proteins and virus proteins from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Regarding the function of NECTIN2 protein in CA, we focused on the ‘bridge function’ of NECTIN2 and CD226 in our protein–protein interaction network analysis (Supplementary Figure 6A). [ 35 ] We found that lipid proteins and inflammatory proteins were linked by the ligand–receptor binding of NECTIN2 and CD226. [ 36 ] As we all know, lipid metabolism plays an important role in CA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the function of NECTIN2 protein in CA, we focused on the ‘bridge function’ of NECTIN2 and CD226 in our protein–protein interaction network analysis (Supplementary Figure 6A). [ 35 ] We found that lipid proteins and inflammatory proteins were linked by the ligand–receptor binding of NECTIN2 and CD226. [ 36 ] As we all know, lipid metabolism plays an important role in CA progression.…”
Section: Discussionmentioning
confidence: 99%
“…We extracted 288,989 experimental interactions between 20,748 HPs (shown in Appendix 1). Different centralities, including degree (connectivity), neighborhood connectivity, shortest paths, closeness centrality, betweenness centrality (16,23), and diversity of predators, were applied (24) to score each HP. In the human-virus PPI network, for each HP, each of the virus families that interacts with it is called a predator.…”
Section: Most Central Lysosomal Genes In Human Ppi Networkmentioning
confidence: 99%
“…One of the ways to identify essential genes that play a vital role in diseases is to analyze the human proteinprotein interaction network (HPPIN) and centrality measures. Centrality is the most critical parameter for identifying the gravity of each gene/protein as a node in networks (16).…”
Section: Introductionmentioning
confidence: 99%
“…Network positions of power have also been used to prioritize potential antiviral drug candidates [ 22 ]. New proposed measures of centrality coined for HPIs to aid in the design of multipurpose drugs include Connectivity of human proteins targeted by same virus protein, propagation speed, diversity of predators, decreased shortest path, component index, crown centrality and vulnerable centrality [ 23 ]. The development of novel drugs, vaccines and other therapeutics for CVDs caused by microorganisms is highly dependent on the knowledge gained from investigating HPIs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%